Association between celiac disease and Crohn's disease - a challenge to the coloproctologist - Iezzi,Leonardo Estenio (2012)
Over the past few years, many studies on the association between celiac disease and inflammatory bowel disease have been reported. The genetic origin of this association has prompted research that searches for a common link for the concomitant manifestation of these pathologies. Clinical studies aim not only to demonstrate this relation, but also to establish the epidemiological frequencies among affected individuals and their relatives as compared to the general population. The similar clinical symptoms, difficulties, diagnoses, and therapeutics are still a challenge, since this association is unknown to most coloproctologists, thereby culminating in treatments and surgical procedures with no benefits for the patient.